Health-related Quality of life among patients with Ankylosing Spondylitis and its correlation with disease-related variables. A Cross-Sectional Study in Erbil City - Dana Abdulkareem Mahmood; Dashty Abbas Albustany (Advanced Medical Journal)
Background and objectives: Ankylosing spondylitis is a chronic, rheumatic, inflammatory disease that basically involves axial skeleton. As a result, functional limitations develop that may negatively affect quality of life. Our aim is to assess the quality-of-life in patients with ankylosing spondylitis and to determine its’ correlation with disease variables including disease activity, functional status, spinal mobility, and bodily pain.